Three new species of Cayratia-like genera (Vitaceae) from Zhejiang, East China - Chen, Zheng-Hai; Chen, Feng; Lu, Yi-Fei; Xie, Wen-Yuan; Jin, Xiao-Feng (Phytotaxa, 2020)
Cayratia s. l. is not a monophyletic genus and is now divided into four genera worldwide, with three genera (Cayratia s. s., Causonis and Pseudocayratia) occurring in China. Recent morphological and molecular analyses of the Cayratia-like species from Zhejiang, East China, revealed three new species. Causonis wentsiana sp. nov. differs from C. japonica in having multicellular-pilose branchlets, leaves, peduncles and petals, petals long-corniculate at the apex. Causonis montana sp. nov. differs from C. japonica in having thick, papery leaf blades, central leaflet with lateral veins 9–12 pairs, margin 12–22-toothed on each side, and seeds acutely rugate both adaxially and abaxially. Pseudocayratia orientalisinensis sp. nov. differs from P. speciosa in having non-branched stems, papery leaf blades with central leaflet broadly obovate-elliptic, broadly elliptic or rhombic-elliptic and short-acuminate to acute apices.